Clinical Learning for Students with the Caregiver Empowerment Program Based-on Adaptation Model (CEP-BAM) in Improving the Quality of Life and Family Ability in Helping the Adaptation of Stroke Patient Training - Agianto Agianto; Bernadetta Germia Aridamayanti; Herry Setiawan; Angga Irawan; Doni Wibowo; Maliwan Silarat; Muhammad Amin Bin Ahmad Zaki (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
ABSTRACTIntroduction: Clinical learning aims to make students independent for the demands of development and the need for competitiveness. However, until now, there has been no clinical learning that can provide learning experience in the field, especially in community-based families of stroke patients that can improve not only knowledge, but also the affective and psychomotor skills of nursing students. This research aims to provide student clinical learning with the concept of Caregiver Empowerment Program Based-On Adaptation Model (CEP-BAM) in improving quality of life and family ability in helping adaptation of stroke patient training.Method: The research used a quasi-experimental study design with a pretest and posttest in the intervention and control groups. Research instruments: Student Knowledge Level Questionnaire, WHOQOL-BREF, Family Role and Responsibilities Instrument. The sample consisted of 2nd semester nursing students (ners profession) and nuclear family members of stroke patients, the 1st attack who were in the rehabilitation stage of 60 respondents (intervention and control) with simple random sampling. Data were analyzed with Wilcoxon signed ranks test and MANOVA. The research was carried out in 4 health center where nursing students practiced for their clinical practice.Results: The p-value of 0.001<0.05 in all groups which means that there is a difference in the average value of the quality of life and the ability of stroke patients' families between the intervention group and the control group.Conclusions: There is a difference in the average value of the intervention and control groups before and after each intervention.